Advances in Nitrogen Fixation Research 1984
DOI: 10.1007/978-94-009-6923-0_305
|View full text |Cite
|
Sign up to set email alerts
|

HETEROGENEITY OF GLUTAMINE SYNTHETASE POLYPEPTIDES IN Phaseolus vulgaris L

Abstract: Glutamine synthetases from roots, nodules, and leaves of Phaseolus vulgaris L. have been purified to homogeneity and their polypeptide composition determined.The leaf enzyme is composed of six polypeptides. The cytosolic fraction contains two 43,000 dalton polypeptides and the chloroplastic enzyme is formed by four 45,000 dalton polypeptides. Root glutamine synthetase consists only of the same two polypeptides of 43,000 dalton that are present in the leaf enzyme. The nodule enzyme is formed by two polypeptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
2
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 12 publications
2
55
2
1
Order By: Relevance
“…Lara et al (13) reported that both GS,, and GSn2 have f and y subunit polypeptides, although the amount of y in GS.2 is relatively small in comparison to (3. This discrepancy between their and our results may be because we have purified GSn2 to homogeneity. Lara The native GS consists of eight subunit polypeptides, and in the root nodules they are of two different types (3,13). We proposed earlier that a total of nine isozymes can be generated assuming the assembly of, and y subunit polypeptides into the holoenzyme is a random process (23).…”
Section: Purification Of Gsn1 and Gsn2mentioning
confidence: 99%
See 3 more Smart Citations
“…Lara et al (13) reported that both GS,, and GSn2 have f and y subunit polypeptides, although the amount of y in GS.2 is relatively small in comparison to (3. This discrepancy between their and our results may be because we have purified GSn2 to homogeneity. Lara The native GS consists of eight subunit polypeptides, and in the root nodules they are of two different types (3,13). We proposed earlier that a total of nine isozymes can be generated assuming the assembly of, and y subunit polypeptides into the holoenzyme is a random process (23).…”
Section: Purification Of Gsn1 and Gsn2mentioning
confidence: 99%
“…A small source is in the infected cells, and a large source is in the uninfected cells, which for the purpose of this discussion are all nodule cells except the infected ones. The (3 polypeptide is found in the leaves, roots, and nodules (7,13). Its gene appears to be constitutively expressed (7).…”
Section: Purification Of Gsn1 and Gsn2mentioning
confidence: 99%
See 2 more Smart Citations
“…Tanto a isoforma da GS presente nas raízes como nas folhas são compostas de polipeptídeos denominados α e β (Lara et al, 1984). Nos nódulos, as subunidades que formam a enzima são do tipo β e α, as quais diferem entre si no ponto isoelétrico, mas não em relação ao tamanho.…”
Section: Glutamato (Glu) + Nhunclassified